IMPROVEMENT OF AWARENESS AND ASPECT OF COMMUNITY PARTICIPATION IN ENVIRONMENTAL MANAGEMENT AND CLIMATE CHANGE ADAPTATION BY ECO-MOSQUE - Auvaria, Shinfi Wazna (Al-Ard: Jurnal Teknik Lingkungan, 2018)
Climate change and environmental pollution are some of the current environmental issues of global concern. One in six people died in 2015 due to environmental pollution. Climate change that occurs can be seen from the recent number of rainy season shift and extreme natural disasters. IPCC’s fifth Assessment report says that there are 95% chance of human activity in the last 50 years is the trigger of climate change. Some means to achieve SDG’s targets and solving environmental problems are increasing awareness and aspects of community participation in the settlement, including adaptation and mitigation of climate change. Some countries with a majority of the population of Muslims, there is Authentic Islamic Environmental Movement. One of the adapted program is EcoMosque as one of the ways to increase awareness and to increase aspects of community participation in overcoming environmental problems in Indonesia. EcoMosque is very possible to be done in Indonesia because supported by the majority of Islamic’s population which is very potential in the implementation